Cultural and Civic Literacy in Elementary Schools: A Bibliometric and Systematic Literature Review - Komara, Intan Budi; Sari, Fitrianti Nur Indah; Darmayanti, Mela (Universitas Trunojoyo Madura, 2025)
The low level of cultural literacy among students is a challenge for all parties, both the government and the school environment, to increase the sense of nationalism. Because cultural literacy will increase the feeling of love for the country and form a young generation that will continue to preserve the cultures that exist in Indonesia. Therefore, promoting cultural literacy among students requires various supports, both from the government, parents, teachers and other elements. This research uses literature review and bibliometric methods from various previous studies to obtain a theoretical basis that is able to solve the problem being researched. This research aims to describe efforts and strategies in implementing cultural literacy in schools by having three implementation programs through extracurricular activities, learning models methods and teacher empowerment. With the efforts implemented, it is hoped that cultural literacy, which is an attitude of national identity, can continue to stick with them.